Ten years later - Götzenbrucker, Gerit; Köhl, Margarita (Eludamos: Journal for Computer Game Culture, 2009)
How does the participation in Massively Multiplayer Online Role-Playing Games (MMORPGs) affect the individual gamer’s self- development and social integration? The results of 1998/99’s empirical study dealing with the topic of “Integrative Potentials of New Technologies” (see Götzenbrucker 2001) already highlighted the fact that differing gaming environments attracted specific types of gamers. These various types of gamers were characterized by different kinds of lifestyles and divergent social positions. The aim of the actual study was to yield new insights into the long-term effects of playing MMORPGs. This was accomplished through interviews with 15 of the online gamers interviewed for 1999’s research project. In the course of the “gamer’s career” the game is gradually inscribed into everyday life through processes of “habitualization” and “ritualization” becoming a part of the gamer’s individual “media menus”. According to the long-term gamers’ diverging motivational sets 4 different types of gamers could be identified varying regarding their focus of playing and strategies of integrating the game into everyday life. Altogether, the findings provide an account of the mutual interference of playing habits and life situation. As activities related to media simultaneously involve time (see Neverla 2007) “time” is playing an important role in the process of incorporating social practices of gaming into every day life. When life situations change due to the transition from a period of education to a period of life determined by work time capacities diminish drastically. This is why the gamers develop specific strategies of adaptation. Another important parameter are “turning points” (for example birth of a child) in the gamers’ lives. Comparison highlighted the fact that the size of the gamers’ formerly large social networks has decreased and their configuration has changed: Although online gamer friends are still forming a big part of the gamers’ social networks (in sum 22% of all existing network-contacts) ex gamers (people who quitted gaming) by trend have less online gamer friends belonging to their social networks then before. Conversely in the still gamers’ networks the number of online gamer friends has increased. In conclusion the interviewees can be characterized as “innovaters” or “early adopters” as well as “pioneers of the digital generation” who form a part of a “technological avant-garde”. They represent a new “media lifestyle” which similarly incorporates the virtual and the real world.